Physicians' Knowledge and Practices Regarding Asthma in Jordan: A Cross-Sectional Study - Dahmash, Eman Z. (Frontiers in Public Health, 2021)
Objectives: Asthma is a chronic noncommunicable disease that causes significant morbidity and mortality and requires ongoing clinical care. Appropriate knowledge by physicians is vital in the management of asthma. Therefore, this study aims to explore and identify the gaps in physicians’ knowledge and practices concerning the management of asthma. Methods: A cross-sectional study using an online survey was conducted in Jordan to understand the gap in knowledge and practices in the management of asthma among physicians. A previously validated questionnaire was employed, the Physicians’ Practice Assessment Questionnaire (PPAQ). The knowledge questions based on the GINA guidelines were used to assess knowledge and practice among the study’s participants. Predictors of good practice were identified using logistic regression. Results: A total of 271 physicians participated in this survey. Overall knowledge among physicians scored above 78%. However, gaps were pertinent in identifying the signs of asthma attacks that accounted for 61.9% of the participants; whereas only 67.6% of the physicians knew the drugs used for the management of asthma. The study revealed alarming results when practices were assessed, with the overall percentage of physicians applying the required practices not exceeding 57.1%±25.7%. Logistic regression analysis to determine predictors of good practice showed that out of several independent variables, physicians who see 6-10 asthma patients per day are five times more likely to follow the guidelines’ recommendations in their practice; senior physicians (> 50 years old) and those who see 1-5 asthma patients daily are around two times more likely to follow guidelines (p 0.001). Conclusions: The findings of this study identify the need to transform knowledge into practice. This could be achieved through the professional education of physicians, constant reminders to physicians in a simple form, and a clinical audit of practice. There is a need for novel knowledge transfer approaches to induce behavioral and practice change towards the management of asthma.